Untangling the Relationship Between Antiretroviral Therapy Use and Incident Pregnancy: A Marginal Structural Model Analysis Using Data From 47, 313 HIV-Positive Women in East Africa. (1st July 2016) - Elul, Batya; Wools-Kaloustian, Kara K.; Wu, Yingfeng; Musick, Beverly S.; Nuwagaba-Biribonwoha, Harriet; Nash, Denis; Ayaya, Samuel; Bukusi, Elizabeth; Okong, Pius; Otieno, Juliana; Wabwire, Deo; Kambugu, Andrew; et al.
Abstract : Background: Scale-up of triple-drug antiretroviral therapy (ART) in Africa has transformed the context of childbearing for HIV-positive women and may impact pregnancy incidence in HIV programs. Methods: Using observational data from 47, 313 HIV-positive women enrolled at 26 HIV clinics in Kenya and Uganda between 2001 and 2009, we calculated the crude cumulative incidence of pregnancy for the pre-ART and on-ART periods. The causal effect of ART use on incident pregnancy was assessed using inverse probability weighted marginal structural models, and the relationship was further explored in multivariable Cox models. Results: Crude cumulative pregnancy incidence at 1 year after enrollment/ART initiation was 4.0% and 3.9% during the pre-ART and on-ART periods, respectively. In marginal structural models, ART use was not significantly associated with incident pregnancy [hazard ratio = 1.06; 95% confidence interval (CI): 0.99 to 1.12]. Similarly, in Cox models, there was no significant relationship between ART use and incident pregnancy (cause-specific hazard ratio: 0.98; 95% CI: 0.91 to 1.05), but effect modification was observed. Specifically, women who were pregnant at enrollment and on ART had an increased risk of incident pregnancy compared to those not pregnant at enrollment and not on ART (cause-specific hazard ratio: 1.11; 95% CI: 1.01 to 1.23). Conclusions: In this large cohort, ART initiation was not associated with incident pregnancy in the general population of women enrolling in HIV care but rather only among those pregnant at enrollment. This finding further highlights the importance of scaling up access to lifelong treatment for pregnant women. Abstract : Supplemental Digital Content is Available in the Text.